2009
DOI: 10.1007/s11010-009-0241-z
|View full text |Cite
|
Sign up to set email alerts
|

The changes in β-adrenoceptor-mediated cardiac function in experimental hypothyroidism: the possible contribution of cardiac β3-adrenoceptors

Abstract: Thyroid hormone deficiency has been reported to decrease expression and function of both beta(1)- and beta(2)-adrenoceptor in different tissues including heart. The purpose of this study was to examine the possible contribution of beta(3)-adrenoceptors to cardiac dysfunction in hypothyroidism. In addition, effect of this pathology on beta(1)- and beta(2)-adrenoceptor was investigated. Hypothyroidism was induced by adding methimazole (300 mg/l) to drinking water of rats for 8 weeks. Cardiac hemodynamic paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…These data indicate that desensitization of β-AR is mainly due to the down-regulation of β 1 -ARs. These results are consistent with past reports, 4,36 but contrary to the findings of Arioglu 7 et al, who reported that decreased positive inotropic responses to both isoprenaline and noradrenaline in isolated papillary muscle but unchanged β 1 -AR mRNA expression in hypothyroidism. Of note, Arioglu’s group was the first to measure hypothyroidism-induced changes in β 3 -AR.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These data indicate that desensitization of β-AR is mainly due to the down-regulation of β 1 -ARs. These results are consistent with past reports, 4,36 but contrary to the findings of Arioglu 7 et al, who reported that decreased positive inotropic responses to both isoprenaline and noradrenaline in isolated papillary muscle but unchanged β 1 -AR mRNA expression in hypothyroidism. Of note, Arioglu’s group was the first to measure hypothyroidism-induced changes in β 3 -AR.…”
Section: Discussionsupporting
confidence: 92%
“…2, 5, 7, 8 Consistent with past experimental and clinical reports, these animals showed increased SNS activation, with significantly decreased heart rate, stroke volume, cardiac output, ejection fraction, and increased Ea without significant change in V ED (Table 1). 3, 4, 31 The relative unchanged V ED may be related hypothyroidism produced LV atrophy.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…A recent study reports a significant increase in ß 3 -AR mRNA expression, although BRL37344-induced negative inotropic effect was decreased [47]. The reduced BRL37344-induced negative inotropic effect could be at least partly explained by alteration of downstream ß 3 -AR signaling pathway.…”
Section: Hypothyroidismmentioning
confidence: 88%